Sonoran mining, a key element in the fulfillment of the 17 Sustainable Development Goals (SDG), in the 2030 agenda - Alegría Murrieta, Maria Ananí (Universidad de Sonora, 2021)
In recent years, the concept of sustainable development (SD) has been strengthened, since its first description adopted by the Bruntland Commission in 1987; Recently, the 195 Members of the United Nations (UN) approved a document entitled “Transforming Our World: The 2030 Agenda, for Sustainable Development (ODS)”, which will be in force during the years 2015 to 2030. Economic, social and environmental growth and development are impacted by various economic activities such as mining, and these not only locally, they transcend borders, clearly these impacts can be used to create new infrastructures, new technologies and opportunities in relationship with the workforce, highlighting that this industry has the opportunity and the necessary potential to contribute positively to the achievement of the 17 Sustainable Development Goals (SDG), in the new 2030 agenda; The objective of this article is to describe and analyze the impact of the 17 SDGs, from the “Economic Development” section or section, specifically SDG 8, 9 and 12, in gold mining in the state of Sonora, with emphasis on the region of Caborca, Sonora, Mexico, in the period from 2008 to 2018.